Pengaruh Cita Rasa dan Emotional Marketing Terhadap Loyalitas Pelanggan (Studi pada Mcdonalds’s Kota Medan) - Dasuha, Timothy W.S.; Marpaung, Nicholas (INDO PUBLISHING, 2026)
This study aims to analyze the effect of taste and emotional marketing on customer loyalty at McDonald’s in Medan City. The rapid growth of the fast-food industry requires companies not only to maintain product quality but also to build strong emotional connections with customers in order to sustain loyalty amid increasing competition.This research is a quantitative study with an associative approach. The population consists of McDonald’s customers in Medan, with a sample of 96 respondents selected using Cochran. Data were collected through questionnaires and analyzed using multiple linear regression with the assistance of SPSS version 25. The results show that: (1) Taste (X1) has a positive and significant effect on Customer Loyalty (Y), with a t-value of 2.853 > 1.986, a significance level of 0.000 < 0.05, and a regression coefficient of 0.218; (2) Emotional Marketing (X2) has a positive and significant effect on Customer Loyalty (Y), with a t-value of 6.983 > 1.985, a significance level of 0.005 < 0.05, and a regression coefficient of 0.402; (3) Taste (X1) and Emotional Marketing (X2) simultaneously have a positive and significant effect on Customer Loyalty (Y), with an F-value of 69.789 > 3.09 and a significance level of 0.000 < 0.05. The Adjusted R Square value of 0.592 indicates that both independent variables explain 59.2% of the variation in customer loyalty, while the remaining 40.8% is influenced by other factors outside this study. The conclusion of this research is that consistent taste quality and appropriate emotional marketing strategies can enhance customer loyalty at McDonald’s in Medan. The practical implication of this study highlights the importance of maintaining product taste while strengthening emotional engagement through customer experience to foster long-term loyalty.